1998
DOI: 10.1007/bf02931696
|View full text |Cite
|
Sign up to set email alerts
|

Social and behavioral factors associated with condom use among female commercial sex workers (CSWs) in tarlac, the Philippines

Abstract: This study examines social and behavioral factors associated with condom use among female commercial sex workers (CSWs) in Tarlac, the Philippines. One hundred and twenty-one CSWs who visited a social hygiene clinic for regular check-ups were asked to fill out a self-administered questionnaire with thirty-one items. More than 80% of the respondents had experience of using condoms with clients. However, only 48% of them used consistently. Six factors, level of education, knowledge of condom application, knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…The association we found between inconsistent condom use with client's indifference or negative personal attitude towards condom use during commercial sex, as well as with deciding on condom use done by clients or by mutual agreement between FSWs and client, were consistent with the results of the studies among FSWs in China, Cambodia, Korea, Sri Lanka, Ghana, and Vietnam, which found similar associations with inconsistent condom use [20][21][22][23][24][25][26][27][28]. Factors involved in the frequent acceptance of commercial sex without condoms probably include lack of authority, fear of losing clients and weak negotiation skills.…”
Section: Discussionsupporting
confidence: 85%
“…The association we found between inconsistent condom use with client's indifference or negative personal attitude towards condom use during commercial sex, as well as with deciding on condom use done by clients or by mutual agreement between FSWs and client, were consistent with the results of the studies among FSWs in China, Cambodia, Korea, Sri Lanka, Ghana, and Vietnam, which found similar associations with inconsistent condom use [20][21][22][23][24][25][26][27][28]. Factors involved in the frequent acceptance of commercial sex without condoms probably include lack of authority, fear of losing clients and weak negotiation skills.…”
Section: Discussionsupporting
confidence: 85%
“… 18 , 31 , 39 In a survey of FSWs in a rural setting, health providers were the primary sources of information on condom use. 33 Health facilities and non-government organizations were reported to provide condom education and free condoms for cisgender-MSM and transgender women. 15 However, it was found that there were facilities that require HIV testing before receiving free condoms.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent use of condoms among FSWs was more evident in establishments with HIV education and condom use policy than those without. 20,21,30,37,39 Manager's advice, 33 favorable manager attitude, 32 and more frequent manager contact 18 were significant factors to consistent use of condoms. Managers who received training on HIV education and support to implement workplace HIV education and prevention policies positively influenced the condom use practices of FSWs.…”
Section: Institutional Factorsmentioning
confidence: 98%
See 2 more Smart Citations